What matters more? What matters less? Changes in the transition to post-secondary between two Toronto high-school cohorts - Robson, Karen; Pullman, Ashley; Maier, Reana; Anisef, Paul; Brown, Robert S. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2021)
Using data from two Toronto student cohorts that entered high school five years apart, this study uses descriptive and multivariate techniques to examine short-term change in the predictors of four possible pathways after high school: confirming a place in university, confirming a place in college, applying but no admittance, or not applying at all. From a comparative cohort perspective, the analysis considers various overlapping ascriptive and school experience factors that contribute to unequal transitions—from race, gender, and immigration background to early achievement, attendance, and suspensions. Even across a short time period, there is change in transition patterns. The results highlight that a comparative cohort approach provides insight into how the transition to post-secondary education in an urban environment changes even over relatively short periods of time.